Evaluation of the friction and wear behavior of a-C:H coatings for lubricant-reduced sheet metal forming - Reblitz, Jonas; Zettl, Bastian; Seynstahl, Armin; Orgeldinger, Christian; Tremmel, Stephan; Merklein, Marion (Materials Research Proceedings, 2024)
Industrial companies are confronted with increasing demands for sustainability, challenges in the availability of raw materials as well as rising energy and labor costs. Thus, technological measures for improving the ecologic and economic potential of production are required. An important production stage for the manufacturing of metal-based products is sheet metal forming which consists of several production steps. Initially, the semi-finished sheets are lubricated with oil to reduce friction in the actual forming stage and afterwards they have to be cleaned. One approach for the decrease of production costs and increase of sustainability is the avoidance or reduction of oil-based lubricants and hence subsequent cleaning of the sheet metal parts. However, reducing the amount of lubrication leads to higher friction and wear. Consequently, the part quality as well as tool lifetime are significantly decreased. To meet these challenges, surface modifications for the reduction of wear can be applied. In this study, diamond like carbon (DLC) tool coatings were combined with minimum quantities of a solid lubricant on semi-finished parts to analyze the potential of the coatings for beneficial friction conditions. In this context, suitable a-C:H coating systems were needed to be identified. The associated friction and wear behavior was evaluated as a function of the lubricant amount for different variants of semifinished parts. Initially, several a-C:H coatings were generated with varying deposition parameters. Promising variants regarding layer adhesion were analyzed for sheet metal forming in terms of tribological behavior. The resulting coefficients of friction (CoF) and wear resistance were investigated with strip drawing tests. For the comparison of the results over different industrially relevant sheet metals, two aluminum alloys as well as one steel material with different zinc coatings were evaluated. For all materials, the amount of solid lubricant was varied in a range below 0.8 g/m2 up to a completely dry condition without lubrication. Introduction
CRIS-Team Scopus Importer:2024-11-08
Keywords: DLC Coatings; Physical Vapor Deposition (PVD); Sheet Metal; Tribology

Evaluation of the properties of AA7020 tubes generated by a heat treatment based hydroforming process - Reblitz, Jonas; Trân, Ricardo; Kräusel, Verena; Merklein, Marion (SheMet2023, 2023)
Energy efficiency and sustainability are getting more and more relevant in society and industry. Especially energy-intensive sectors offer a high potential for power savings. Thus, different lightweight strategies are applied in the automotive sector. In this context, high strength profile components are used as crash structures. As an example, these profiles are deployed to protect the battery of electrically powered vehicles. Therefore, high strength aluminum alloys of the 7xxx series are suitable for compensating the high battery weight partly. Compared to steel, this material is characterized by a high strength-to-weight ratio as well as an increased thermal conductivity. However, one challenge in forming high strength aluminum alloys is the limited formability at room temperature. For this purpose, heat treatment based process routes for tube hydroforming are investigated within this research work. By the combination of W-temper forming and hydroforming complex part geometries can be generated. A subsequent artificial ageing process realizes the required high strength of the profiles. Using AA7020 tubes, the properties of a demonstrator geometry are compared to the initial state T6 of the semi-finished parts. For this purpose, the wall thickness distribution and the grain structure are evaluated. Thereby, the influence of forming and heat treatment on the geometrical and microstructural properties is to be analyzed. For the evaluation of the achievable hardening of the aluminum alloy, the mechanical properties are investigated by tensile tests. This investigations provide an assessment of the process route under industry-related conditions.<br
Keywords: Heat Treatment; Hydroforming; Tubes

Experimental investigations on a process adapted material testing method for hydroforming of tubular components - Reblitz, Jonas; Merklein, Marion (SheMet2025, 2025)
In the automotive sector, an important strategy for reducing CO2 emissions is lightweight construction. In this regard, body-in-white parts offer a high potential for weight reduc-tions by substituting conventional steel parts with tubular, aluminum-based components. Due to their high strength-to-weight-ratio and high crashworthiness, tube profiles are often used as safety-relevant car body components. As lightweight design becomes increasingly important, complex part geometries are required, which can be realized by hydroforming. Especially for structural components, an exact determination of the material properties is necessary, in order to achieve a high prediction accuracy of FE-simulations. Thus, a failure-free component production has to be enabled. However, due to a varying stress and strain state, the tensile test according to DIN EN ISO 6892 as a standard characterization method is only insufficiently suitable for the characterization of tube profiles for a hydroforming process. For this purpose, a new testing method has been developed and investigated within this paper, which provides new insights regarding the material behavior of tubular components. The testing-rig is based on a bulge test, which reproduces the stress and strain state of a hydroforming process. By comparing the results of the material characterization with those of a tensile test, the differences in the mechanical properties depending on the testing method are evaluated. During the test, the surface strains and the internal pressure are varied and recorded. Based on these findings, a more accurate prediction of FE-simulations is aspired in future research wor
Keywords: Hydroforming; Aluminum; Tube Bulge Test

Hydroforming of High-Strength Aluminum Tubes with Thermo-Mechanical Manufacturing Processes - Trân, Ricardo; Reblitz, Jonas; Haase, Rico; Psyk, Verena; Kräusel, Verena; Merklein, Marion (Engineering Proceedings, 2022)
The amount of complex profile components in car bodies increases due to the emerging electromobility. High-strength aluminum alloys are ideally suited as material for automotive applications due to their extraordinary lightweight construction potential. The presented study focuses on the transfer of established thermo-mechanical manufacturing processes for sheet metal components to hydroforming of tube material. Demonstrator components are produced from EN AW-7020 using W-temper-forming and hot forming and compared numerically and experimentally. The results show that the determined material properties are sufficiently accurate to numerically represent the temperature-supported processes with excellent precision. The formed components can be used to demonstrate the potential of hydroforming for high-strength aluminum tubes using W-temper-forming and hot forming.
Created from Fastlane, Scopus look-up
Keywords: aluminum; finite element method (FEM); heat treatment; hydroforming; metal forming

Investigation of Geometrical and Microstructural Influences on the Mechanical Properties of an Extruded AA7020 Tube - Reblitz, Jonas; Wiesenmayer, Sebastian; Trân, Ricardo; Merklein, Marion (Lecture Notes in Production Engineering, 2023)
In the automotive sector, an important strategy for reducing CO2- emissions is lightweight construction. In this regard, body-in-white parts offer a high potential for weight reductions by substituting conventional steel parts with tubular, aluminum-based components. Due to their high strength-to-weightratio and high crashworthiness, tube profiles are often used as safety-relevant car body components. Therefore, an exact determination of the material properties is necessary, in order to achieve a high prediction accuracy of FE-simulations. In contrast to the testing of flat semi-finished parts, there are only few standardized methods for the material characterization of tubular components. Furthermore, a profound knowledge regarding the influences of geometry and manufacturing process of the tube profiles on the material properties has to be gained. Thus, AA7020 tubes are analyzed in this research work. Tensile specimens are cut out of a tube by a laser-cutting machine. As a result, the cross-section of the samples is curved as well. To ensure a proper material testing, the clamping jaws for the tensile test are adjusted to the curvature of the samples. For the characterization of the tube properties, caused by the manufacturing process, optical measurements are performed. The mechanical properties of the different grain structures are determined by the thermo-mechanical simulator Gleeble 3500 in T6 condition. Therefore, tensile specimens with a reduced wall thickness are prepared. Afterwards the curved tensile samples are tested in T6 and W-temper condition. To validate the comparability of the determined material properties, a comparison is conducted with flat specimens prepared from the semi-finished tube profiles.<br
Keywords: Material characterization; W-temper condition; Tubes

Investigation of Geometrical and Microstructural Influences on the Mechanical Properties of an Extruded AA7020 Tube - Reblitz, Jonas; Wiesenmayer, Sebastian; Trân, Ricardo; Merklein, Marion (Production at the Leading Edge of Technology, 2023)
In the automotive sector, an important strategy for reducing CO2-emissions is lightweight construction. In this regard, body-in-white parts offer a high potential for weight reductions by substituting conventional steel parts with tubular, aluminum-based components. Due to their high strength-to-weight-ratio and high crashworthiness, tube profiles are often used as safety-relevant car body components. Therefore, an exact determination of the material properties is necessary, in order to achieve a high prediction accuracy of FE-simulations. In contrast to the testing of flat semi-finished parts, there are only few standardized methods for the material characterization of tubular components. Furthermore, a profound knowledge regarding the influences of geometry and manufacturing process of the tube profiles on the material properties has to be gained. Thus, AA7020 tubes are analyzed in this research work. Tensile specimens are cut out of a tube by a laser-cutting machine. As a result, the cross-section of the samples is curved as well. To ensure a proper material testing, the clamping jaws for the tensile test are adjusted to the curvature of the samples. For the characterization of the tube properties, caused by the manufacturing process, optical measurements are performed. The mechanical properties of the different grain structures are determined by the thermo-mechanical simulator Gleeble 3500 in T6 condition. Therefore, tensile specimens with a reduced wall thickness are prepared. Afterwards the curved tensile samples are tested in T6 and W-temper condition. To validate the comparability of the determined material properties, a comparison is conducted with flat specimens prepared from the semi-finished tube profiles.<br
Keywords: Material characterization; W-temper condition; Tubes

Numerical and experimental investigations on the mechanical properties of milled specimens from an AA7020 tube - Reblitz, Jonas; Reuther, Franz; Trân, Ricardo; Kräusel, Verena; Merklein, Marion (Achievements and Trends in Material Forming, 2022)
The reduction of weight is crucial in the automotive sector to reach a lower energy consumption and an increased range, especially for electrically powered vehicles. In this regard, body-in-white parts offer a high potential for the application of lightweight construction. The required weight savings can be achieved by implementing parts with a high strength-to-weight ratio. A promising approach is the combination of lightweight materials and lightweight design, which can be realized by tubular components made of high strength aluminum. Due to their structural stiffness and high crashworthiness, those structures are often used as safety-relevant car body components. However, the material characterization of tube profiles is a major challenge, which in turn impedes an accurate numerical simulation and precise process design. In contrast to flat semi-finished parts, various effects of the production process and the geometry, regarding the stress state under load, must be taken into account. For this purpose, adapted testing methods considering the geometrical and mechanical properties of the tubular parts have to be investigated, in order to generate an accurate material model and process design. Within this research work, tubular components made out of AA7020 in W-temper condition were used to analyze the mechanical properties. In this regard, several tensile specimens are milled from a tube, so they also have a curvature profile. The experimental tensile tests have been performed at different strain rates by using a universal testing machine from type Gleeble 3500. To ensure a proper measurement of the mechanical properties, the clamping jaws of the testing machine are adjusted to the curved samples. The investigated material parameters are subsequently transferred to an FE model with curved specimen to enable an accurate prediction of the forming behavior. In addition, an FE model of a flat tensile specimen was also created for comparison, in order to gain a profound knowledge regarding the influence of the geometric and mechanical properties of tubular components. <
Keywords: Material characterization; W-temper condition; tensile test; tubes